Teacher Perceptions of the Implementation of Curriculum Thematic Learning in 2013 in Sarudik District, Central Tapanuli Regency, Academic Year 2022/2023 - Demmu Karo-Karo; Febby Natasya Simatupang (PT FORMOSA CENDEKIA GLOBAL, 2023)
The problem in this study is how the teacher's perception of the implementation of thematic learning in the 2013 curriculum in Sarudik District, Central Tapanuli Regency. The purpose of this study was to determine the perceptions of elementary school teachers on thematic learning of the 2013 curriculum in Sarudik District, Central Tapanuli Regency. This research is quantitative descriptive. The population in this study were 96 SDN teachers in Sarudik District. The sample in this study used a purposive sampling technique with samples namely SD Negeri 154499 Sarudik 2, SD Negeri 158501 Sibuluan, SD Negeri 158496 Pondok Batu, SD Negeri 152987 Sipan, a total of 50 teachers. The research instrument used was a questionnaire and documentation. The results of this study indicate that the perceptions of elementary school teachers in the thematic learning of the 2013 curriculum in Sarudik District, Central Tapanuli Regency are classified as Good with an average answer score of 3.07.